PELATIHAN MICROSOFT EXCEL BAGI PERANGKAT DESA KRAKITAN KLATEN UNTUK MENDUKUNG PENGELOLAAN ADMINISTRASI DESA BERBASIS TEKNOLOGI KOMPUTER - hendro, Hendro Joko Prasetiyo; Windarti, Mariana; Suradi, Agustinus; Yusuf, Mahmud; Setyawan, Doni (LPPM Universitas Widya Dharma Klaten, 2023)
The use of computer technology in the field of village administrative management is very important, so that the services provided to the community can run more effectively and optimally. Microsoft excel especially Word makes it easy to complete all activities related to community service needs,Human resources in this case are village officials in Krakitan Village, Bayat District, Klaten Regency need to know and be able to utilize technology to support daily operational performance and to improve the quality of service to the community, this needs to be done so that they are not left behind by the pace of technological development. Improving the quality of village apparatus resources is very necessary, because now and in the future the mastery of information technology is needed to support the tasks of village officials